الخارطة الذهنية عند المفسرين في التعامل مع النص القرآني = The mental map of the exegetes in dealing with the Quranic text - Bugrein, Amna; Elatrash, Radwan Jamal Yousef (World Fatwa Management and Research Institute (INFAD) at Universiti Sains Islam Malaysia (USIM), 2019)
This research aims to study and analyze the mental map in some ancient and contemporary exegetes; by answering two main questions: What are the differences between mental maps of ancient and contemporary exegetes? How do we combine them to develop a sophisticated mental map to deal with the Qur'anic text? .The research has followed the method of inductive analytical, and has reached the following results: The possibility of exploiting the mental map in making the Islamic sciences easier and clearer. The mental map, which clarify and explain the exegetes approach followed by each of the exegetes studied, when analyzing mental maps for them, the study found that the ancient exegetes are embarrassed to interpret in their opinion only, They often quote the sayings of the Salaf in the interpretation, Their explanations are limited to weighting and expression, but their opinion is limited. As for the later exegetes found that their quotations are far less than the ancient exegetes. And their interpretations are characterized by the elicitation and analysis of the meaning of the Quran. The study also suggested a mental map that could contribute to making the interpretation of the Quran more accessible and understandable to Muslims, especially in proportion to the present time. *********************************************************** يهدف هذا البحث إلى دراسة وتحليل الخريطة الذهنية عند بعض المفسرين المتقدمين والمتأخرين؛ من خلال الإجابة على سؤالين رئيسين؛ هما: ما هي الاختلافات بين الخرائط الذهنية للمفسرين المتقدمين والمتأخرين؟ وكيف نمزج فيما بينها لوضع خارطة ذهنية متطورة للتعامل مع النص القرآني؟ وقد اتبع الباحثان المنهج الاستقرائي التحليلي، وقد توصل البحث إلى جملة من النتائج أهمها: إمكانية استغلال الخارطة الذهنية في جعل العلوم الإسلامية أكثر سهولة ووضوحاً، تم استنباط الخارطة الذهنية التي توضح وتفسر المنهج التفسيري الذي اتبعه كل مفسر من المفسرين محل الدراسة. عند تحليل الخرائط الذهنية لهم وجدت الدراسة أن المفسرين المتقدمين يتحرجون من التفسير بالرأي المجرد، فكثيرا ما يوردون أقوال السلف في التفسير، وتفسيراتهم تقتصر على الترجيح والإعراب أما رأيهم فهو محدود، أما العلماء المتأخرين فنجد أن استشهادهم بالمأثور أقل بكثير من المفسرين المتقدمين وتفاسيرهم تتسم بالاستنباط والتحليل لمعاني كتاب الله عز وجل. وقد توصلت الدراسة أيضا إلى اقتراح خارطة ذهنية يمكن ان تساهم في جعل تفسير القرآن أكثر يسر وفهم للمسلمين خصوصا بما يتناسب مع الوقت الحالي